2014
DOI: 10.1002/mrm.25483
|View full text |Cite
|
Sign up to set email alerts
|

On the RF heating of coronary stents at 7.0 Tesla MRI

Abstract: The proposed analytical approach can be applied for any patient, coronary stent type, RF coil configuration and RF transmission regime. The generalized approach is of value for RF heating assessment of other passive electrically conductive implants and provides a novel design criterion for RF coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 56 publications
3
61
0
1
Order By: Relevance
“…Results were in agreement for all 6 shims, with errors between simulations and measurements up to 21% on average, potentially due to the unknown exact dimensions of the body coil. These errors are in agreement with other E‐field measurements found in the literature . These results confirm the trend found in the psSAR maps, with shims generating substantially larger E‐fields when channel 1 was dominant.…”
Section: Resultssupporting
confidence: 92%
“…Results were in agreement for all 6 shims, with errors between simulations and measurements up to 21% on average, potentially due to the unknown exact dimensions of the body coil. These errors are in agreement with other E‐field measurements found in the literature . These results confirm the trend found in the psSAR maps, with shims generating substantially larger E‐fields when channel 1 was dominant.…”
Section: Resultssupporting
confidence: 92%
“…UHF sites tend to be cautious with respect to the higher resonance frequency, the various transmit radiofrequency (RF) coils, and the fact that 7T MRI currently is not medically indicated. Nevertheless, some UHF sites already have performed dedicated safety tests for passive implants or have included carefully selected subjects with implants . Because manufacturers only have verified MRI of patients with implanted aneurysm clips to be conditional for some clips in an MR environment up to 3T, a detailed compliance test for 7T is a prerequisite before any examination.…”
Section: Introductionmentioning
confidence: 99%
“…Although SAR has been routinely used as an indirect quantitative measurement for clinical MRI procedures when conductive implants are present , some studies have shown that reported whole‐body SAR values that lead to the same temperature rise in implants significantly varied across different MRI scanners . Moreover, local SAR values do not always directly translate to temperature rise because factors such as thermal conduction and perfusion should be taken into account . Consequently, when it comes to patient safety, temperature calculations/measurements should be considered instead of SAR monitoring alone.…”
Section: Resultsmentioning
confidence: 99%